Evidence for an extinct lineage of angiosperms from the Early Cretaceous of Patagonia and implications for the early radiation of flowering plants - Coiro, Mario (2020)
The pinnately lobed Aptian leaf fossil Mesodescolea plicata was originally described as a cycad, but new evidence from cuticle structure suggests it is an angiosperm. Here we document the morphology and cuticle anatomy of Mesodescolea and explore its significance for early angiosperm evolution. We observed macrofossils and cuticles of Mesodescolea with light microscopy, SEM, and TEM and used phylogenetic methods to test its relationships among extant angiosperms.Mesodescolea has chloranthoid teeth and tertiary veins forming elongate areoles. Its cuticular morphology and ultrastructure reject cycadalean affinities, while its guard cell shape and stomatal ledges are angiospermous. It shares variable stomatal complexes and epidermal oil cells with angiosperm leaves from the lower Potomac Group. Phylogenetic analyses and hypothesis testing support its placement within the basal ANITA grade, most likely in Austrobaileyales, but it diverges markedly in leaf form and venation. Whereas many Early Cretaceous angiosperms fall within the morphological range of extant taxa, Mesodescolea reveals unexpected early morphological and ecophysiological trends. Its similarity to other Early Cretaceous lobate leaves, many previously identified as eudicots but in some cases predating the appearance of tricolpate pollen, may indicate that Mesodescolea is part of a larger extinct lineage of angiosperms.